Shariah minds in Islamic finance: an inside story of a Shariah scholar, by Mohd Daud Bakar, Amanie Media, 2016, xl + 322 pp., ISBN 978-967-13789-0-8 - Ariffin, Muhammad Irwan (IIUM Press, International Islamic University Malaysia, 2017)
This book is a pioneer in providing an insight into the mind of a Shariah scholar from an insider’s perspective. Another special thing about the book is that it is written by Dr. Mohd. Daud Bakar, whom I consider to be an authoritative figure and genuine example of a Shariah scholar in Islamic finance. He has been actively involved in many fundamental works that shape the current world of Islamic finance since the past two decades. Reading the book convinced me that the author is very passionate and sincere in developing a better financial industry that fulfills the Shariah requirement.